Increasing Importance of Positioning in Retailing in the Context of New Competitive Situation Formed by the Eu Integration - Ivanauskas, Robertas; Urbonavičius, Sigitas (Ekonomika, 2003)
Marketing mix of retail companies has some specifics comparing to these of manufacturing and service companies. Price-based competition is rather popular among retailers, since price is one of the marketing elements that are relatively easy to change in retailing. One of the impacts of EU accession processes for Lithuanian retail companies would be increasing competition in this sector. For this reason price-based competition would be not sufficient tool for survival. Retail companies would have to look for new alternatives to compete. Positioning strategy development and implementation seems to be one of possibilitics, since such a strategy would integrate marketing mix elements towards desired position in a much more efficient way. Positioning strategy is proactive by its nature, and can enhance retailer’s differentiation as well as generate continuous improvement of company’s image the target market. All this would result in growing clients’ loyalty and improving financial results of retail company.